PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN MELALUI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI PERIODE 2021-2023 - Anggara Sari, Shella; Faisol; Linawati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
This research is motivated by the importance of sustainability in the operations of energy sector companies, which face high environmental and social risks, while their financial performance remains inconsistent. The study aims to analyze the influence of Environmental, Social, and Governance (ESG) disclosure on financial performance, proxied by Return on Assets (ROA), both directly and indirectly through firm value, proxied by Price to Book Value (PBV). The environmental variable is proxied by carbon emission intensity, the social variable by Corporate Social Responsibility (CSR) expenses, and the governance variable by the proportion of independent commissioners. A causal quantitative approach is applied using secondary data from financial, sustainability, and annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample consists of 69 observations obtained through purposive sampling. Data were analyzed using panel data regression with the Random Effect Model (REM) and Sobel test for mediation. The results show that ESG disclosure does not significantly affect ROA, either directly or indirectly through PBV. These findings indicate that ESG disclosure has not yet created a direct financial impact nor improved firm value in the energy sector.